Pengembangan Panduan Layanan Bimbingan Kelompok untuk Meningkatkan Kebermaknaan Hidup Siswa dalam Pencegahan Penyalahgunaan Narkoba - Rifda Hayati; Firman Firman; Afdal Afdal (Jurnal Neo Konseling, 2021)
The increasing problem of drug abuse among vocational high school students is more worrying. The one that causes drug abuse happen is low meaning of students’ life. The increasing of the meaning of students’ life in drug abuse prevention can be done through group guidance service that held by counseling teachers use the appropriate media and material. This research is development research with the ADDIE model (Analyze, Design, Development, Implementation and Evaluation). The research subject is the vocational high school students and the counseling teachers at school. Validation guide is six experts who validated service guidelines about the material and the display of service guide, the usability test was done by three counseling teachers as well. Data analysis used is descriptive analysis to describe the data about meaning students’ of life in drug abuse and qualitative data analysis to portray the compliance of group guidance for increasing the meaning of students’ life in drug abuse prevention and non-parametric with coefficient statistical test by Kendall (W). The results of the research show that: (1) the level of the meaning of students' life in drug abuse prevention tends to be low, (2) the implementation of group guidance is still limited to overcome the problem of drug abuse, counseling teachers are not skilled yet at compiling the guidelines as a media for group guidance services to increase the meaning of students' life in preventing the drug abuse, (3) the\ level of material appropriateness is in the very feasible category with a percentage of 92% and the appearance of the guide is in the very feasible category with a percentage of 92%, the level of guide use by counseling teachers is in the very good category with a percentage of 87%. There is a significant increase in the meaning of students' life in preventing drug abuse after the implementation of the guidelines, it means that these guidelines can be used by counseling teachers as the material for implementing group guidance services to increase the meaning of students' life in preventing drug abuse.